ANALISIS PENGENDALIAN KUALITAS PRODUK TELUR ASIN PADA UD. SARI LUWIH DI DESA PADANG LUWIH - Candrawati, Angela Ayu Dewi; Nurcaya, I Nyoman (E-Jurnal Manajemen; Vol 9 No 6 (2020)DO - 10.24843/EJMUNUD.2020.v09.i06.p14, 2020)
Good quality in the production process, with predetermined standards will minimize damaged products. The study was conducted at UD. Sari Luwih is a manufacturing and trading company that processes and sells salted egg products. This study aims to determine the quality control system of salted egg production processes at UD. Sari Luwih is optimal or not. Research is descriptive with a qualitative approach. The sampling method is by census technique. The data used in this study, is the data on the number of damaged salted egg products in the period from October to November 2019 with a sample of 37,500 eggs saturated. The analysis technique used is statistical quality control (SQC) using Check sheets, P-charts, Fishbone diagrams, and Quality cost. The results of the analysis using the P-chart show the amount of product damage that is beyond the control limits and requires more control, whereas for quality costs in 2019, the company's actual cost of quality is Rp. 21,210,696.89 is greater than the optimum quality cost where the cost is Rp. 17,389,652.10 shows that the cost of quality control has not yet reached the optimal level. Keywords: quality cost; quality; statistical quality control; SQC.